Quantitative analysis of localized stresses in irradiated stainless steels using high resolution electron backscatter diffraction and molecular dynamics modeling. (15th April 2016) - Johnson, D.C.; Kuhr, B.; Farkas, D.; Was, G.S.
Abstract: Quantitative measurements of stress near dislocation channel–grain boundary (DC–GB) interaction sites were made using high resolution electron backscatter diffraction (HREBSD) and have been compared with molecular dynamics (MD) simulations. Tensile stress normal to the grain boundary was significantly elevated at discontinuous DC–GB intersections with peak magnitudes roughly an order of magnitude greater than at sites where slip transfer occurred. These results constitute the first measurement of stress amplification at DC–GB intersections and provide support to the theory that high normal stress at the grain boundary may be a key driver for the initiation of irradiation assisted stress corrosion cracks. Graphical abstract: